Impact of an Oral Health Education Workshop on Parents' Oral Health Knowledge, Attitude, and Perceived Behavioral Control among African Immigrants. (23rd June 2014) - Amin, Maryam; Nyachhyon, Pawan; Elyasi, Maryam; Al-Nuaimi, Muhammed
Abstract : Purpose . To evaluate the impact of an educational workshop on parental knowledge, attitude, and perceived behavioral control regarding their child's oral health. Materials and Methods . A one-time oral health education workshop including audio/visual and hands-on components was conducted by a trained dentist and bilingual community workers in community locations. Participants were African parents of children who had lived in Canada for less than ten years. The impact of the workshop was evaluated by a questionnaire developed based on the theory of planned behavior. Results . A total of 105 parents participated in this study. Participants were mainly mothers (mean age35.03 ± 5.4 years) who came to Canada as refugee (77.1%) and had below high school education (70%). Paired t -test showed a significant difference in participants' knowledge of caries, preventive measures, and benefits of regular dental visits after the workshop ( P value < 0.05 ). A significant improvement was also found in parental attitudes toward preventive measures and their perceived behavioral control (P < 0.05 ). Parents' intention to take their child to a dentist within six months significantly altered after the workshop ( P value < 0.05 ). Conclusions . A one-time hands-on training was effective in improving parental knowledge, attitude, perceived behavioral control, and intention with respect to their child's oral health and preventive dental visits in African immigrants.